Adapting Psychosocial Interventions for Substance Use Disorders and HIV in Post-COVID-19 Rehabilitation (Bangladesh Journal of Infectious Diseases, 2025)
Background: The COVID-19 pandemic has strengthened the challenges that individuals with substance use disorders (SUDs) face and that those living with HIV experience thus this underscores the need for more adapted psychosocial interventions in post-COVID-19 rehabilitation.Objective: The purpose of the study was to evaluate and explore psychosocial interventions regarding SUDs and HIV to improve treatment effectiveness along with continuity of care in the post-pandemic context.Methodology: This mixed methods design with three phases was applied. The phases included: (1) review systematically of literature about psychosocial SUD and HIV interventions from 2010 to 2023; (2) interviews qualitatively using methods semi-structured with 20 professionals and 20 patients to find adaptations and barriers during the pandemic; and (3) survey quantitatively with 200 patients (120 with SUDs, 40 with HIV, and 40 with both) measuring outcomes, satisfaction, and engagement of treatment. The Treatment Engagement and Retention Scale (TERS), and also the Client Satisfaction Questionnaire (CSQ-8), and additionally the Brief Addiction Monitor (BAM), plus the HIV Treatment Adherence Scale (HTAS) were all standardized tools that were used for it.Results: Cognitive-behavioral therapy, motivational interviewing, and contingency management are psychosocial interventions that greatly reduced how often and how severely people used substances (p < 0.01). Among participants that had HIV, participants did adhere in relation to antiretroviral therapy while improving from 60% up to 85%, thus reducing viral load markedly (p < 0.01). Qualitative findings stressed telehealth was effective overall. They also showed treatment approaches involved personalization such that social support networks strengthened even now. The participants highlighted major benefits that include greater access along with continuous care showing much satisfaction.Conclusion: Psychosocial interventions can be adapted by way of a telehealth integration, in terms of a personalized care, as well as with respect to an improved social support systems. This gives one useful method for better recovery results for persons who are having SUDs as well as HIV after COVID-19.Bangladesh Journal of Infectious Diseases, June 2025;12(1):108-115